Coregistered Spectral Optical Coherence Tomography and Two‐Photon Microscopy for Multimodal Near‐Instantaneous Deep‐Tissue Imaging. Issue 5 (15th April 2020) - Rakhymzhan, Asylkhan; Reuter, Lucie; Raspe, Raphael; Bremer, Daniel; Günther, Robert; Leben, Ruth; Heidelin, Judith; Andresen, Volker; Cheremukhin, Sergey; Schulz‐Hildebrandt, Hinnerk; Bixel, Maria G.; Adams, Ralf H.; et al.
Abstract: Two‐photon microscopy (2PM) has brought unique insight into the mechanisms underlying immune system dynamics and function since it enables monitoring of cellular motility and communication in complex systems within their genuine environment—the living organism. However, use of 2PM in clinical settings is limited. In contrast, optical coherence tomography (OCT), a noninvasive label‐free diagnostic imaging method, which allows monitoring morphologic changes of large tissue regions in vivo, has found broad application in the clinic. Here we developed a combined multimodal technology to achieve near‐instantaneous coregistered OCT, 2PM, and second harmonic generation (SHG) imaging over large volumes (up to 1, 000 × 1, 000 × 300 μm 3 ) of tendons and other tissue compartments in mouse paws, as well as in mouse lymph nodes, spleens, and femurs. Using our multimodal imaging approach, we found differences in macrophage cell shape and motility behavior depending on whether they are located in tendons or in the surrounding tissue compartments of the mouse paw. The cellular shape of tissue‐resident macrophages, indicative for their role in tissue, correlated with the supramolecular organization of collagen as revealed by SHG and OCT. Hence, the here‐presented approach of coregistered OCT and 2PM has the potential to link specific cellular phenotypes and functions (as revealed by 2PM) to tissue morphology (as highlighted by OCT) and thus, to build a bridge between basic research knowledge and clinical observations. © 2020 The Authors. Cytometry Part A published by Wiley Periodicals, Inc. on behalf of International Society for Advancement of Cytometry.